The Examine of Topics and ASEAN Tourist Destination on YouTube Video’s Comment in Year 2023 by using Data Mining Technique - Mekthanavanh, Vinath; Saycocie, Souphilack; Simmavong, Southeva; Khieovongphachanh, Vimontha; Bouddy, Somphong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research has tested the comments posted on YouTube videos about tourist places in ASEAN country in 2023 to define strategies for sustainable tourism development by identifying topics that are discussed about ASEAN countries, providing valuable tourism information and impressive tourist attractions. The data was collected during the period from September 2022 to September 2023 totally 98,238 comments by selecting only English through YouTube’s API and data processing is done by using word association techniques. The results show that the most discussed topics are country, tourist, people, places, tourism, sightseeing, travel, sight, life, and live which are the focus of the perception comments and represent the attraction factors shown by the video and the emotions perceived in comments. The comments are effective for tourism, people, destinations and popular countries which include Indonesia, Laos, Malaysia, Myanmar, Philippines and Singapore. The result of this research demonstrate that this valuable information may become as references for tourism company in these countries for plan development of sustainable tourism of their own.